2004
DOI: 10.1002/kpm.211
|View full text |Cite
|
Sign up to set email alerts
|

E‐learning: a service offering

Abstract: In Finland, both public and private organizations are actively applying information and communication technology (ICT) in adult education. Providing ICT-supported education, e-learning, requires focus on the virtual setting, but also on physical and human factors. Studying the e-learning phenomenon from a service perspective gives new insights into how to provide better learner satisfaction.The article presents a qualitative two-case study. The cases come from Finnish organizations: one case from a polytechnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Moisio and Riitta, 2004). In particular, it was confirmed that the educators should assist users to recognise the value (usefulness) of the e-learning programmes and assist in making them easy to use.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moisio and Riitta, 2004). In particular, it was confirmed that the educators should assist users to recognise the value (usefulness) of the e-learning programmes and assist in making them easy to use.…”
Section: Discussionmentioning
confidence: 56%
“…According to Moisio and Riitta (2004) e-learning is a complex activity which combines a mix of both face-to-face and online activities. Their study revealed a gap between tutor expectations on learner behaviour and the actual learner behaviour.…”
Section: Preliminaries and Background Materialsmentioning
confidence: 99%
“…Second, as was discussed in the Theoretical Foundation section, PBL is most often associated with groups, although Moisio and Smeds (2004) found that students can and do work alone for part of a PBL task. Additional research might investigate how this type of class could employ PBL using groups of students, perhaps even examining group size to determine if that variable might make a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it might be argued that some of the PBL benefits might be lost due to the lack of group interaction. However, one PBL study stated that students worked alone for much of the task (Moisio & Smeds, 2004). Also, Harland (1998) pointed out that students who work together in groups or teams can encounter difficulties that include differential workloads and failing to delegate properly, implying that team‐oriented assignments are not necessarily perfect.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Further, e‐learning does not have the same time and space limitations and also has the potential to address regulatory compliance, meet business needs, retrain employees, and offer customer support, all with a low recurring cost. According to Moisio and Smeds (2004), the rise of e‐learning has had an interesting side effect in some organizations: it has forced management and instructors to rethink the training process. E‐learning is believed to have an important role in empowering learners with employees having on‐demand access to asynchronous learning at any convenient time.…”
Section: Potential Benefits and Drawbacks Of E‐learningmentioning
confidence: 99%